Specific Deletion Occurring in the Directed Evolution of 6-Phosphogluconate Dehydrogenase in ESCHERICHIA COLI - Miller, Raymond D. (1984)
A novel genetic change leading to increased activity of 6-phosphogluconate dehydrogenase (6PGD) in E. coli has been observed. The mutation is a deletion of approximately 0.4 kilobase pairs occurring between the structural gene of 6PGD (gnd) and one copy of an insertion element (IS5 ) found normally in E. coli K12 a few hundred base pairs upstream (counterclockwise) from gnd at 44 minutes on the conventional genetic map. The deletion is associated with a threefold higher activity of 6PGD and a 57% increase in the maximum growth rate when cells are grown in gluconate.